Psychological Characteristics of DecisionMaking in Management - Sharafitdinov Abdulla; Qurbonboyev Miraziz Zulxaydar o‘g‘li (Global Scientific Publishing, 2022)
This article outlines the specifics of decision-making in the management process. It outlines the identity of the manager and the qualities that need to be formed in him and the factors that affect the management process.
Keywords: Contextual model; bjective situation; ehtiros; sympathy